Teaching-Learning Strategy During the Covid-19 Pandemic: Learning With the Correspondence - Eva Luthfi Fakhru Ahsani; Mela Mulyani (Al-Aulad: Journal of Islamic Primary Education, 2022)
This study aims to describe the strategic constraints during the co-19 pandemic, analyze learning models for students, and provide learning solutions with correspondence models. This research method uses a qualitative method with data collection techniques through library research. The results of the study found that teaching and learning strategies during the co-19 pandemic in addition to using online learning educators can use the correspondence model. as a professional educator can implement learning strategies that are appropriate to the conditions and also the situation. Correspondence model is a model of distance learning between educators and students with each other. This research is expected to be able to provide a solution for educators in teaching amid covid-19 pandemi